Relationship between emotional, intelligence, motivation and logical reasoning towards academic achievement among secondary school students - Mohd Noor, Nur Fadzlillah Amira; Hassan, Aminuddin; Ahmad, Nor Aniza (Human Resource Management Academic Research Society, 2017)
The main purpose of this study is to examine the relationship between Emotional Intelligence, Motivation and Logical Thinking of secondary school students in their academic achievement. The emotional intelligence, motivation, and logical thinking of a student play an important role in the mastery of each subject that is learned by it. In the learning process it includes important components such as cognitive and behaviour which also involves the emotion, motivation and thinking of a student. The researchers use stratified random sampling for sampling procedures. In addition, the sample used by the researcher was composed in secondary school students in Johor where the number of clusters was determined according to districts that could be made at random. The researcher selected Form 4 students throughout Johor. This refers to the Cognitive Development Theory proposed by Jean Piaget which is Form 4 student at the aged of 16 years. Demographic information is collected from participants about gender, age, race, and religion and speech language using demographic data forms. Participants will complete four parts of the questionnaire: Emotional Intelligence Self-Assessment (Schutte, 1998), Students Work Preference Inventory (SWPI) built by Amabile, TM (1987), The Group Assessment of Logical Thinking (GALT) Roadrangka, Yeany and Padilla (1983) and academic achievement of students based on PT3 results. The findings show that the correlation coefficient between emotional intelligence and academic achievement is r = - 1.62 at the significance level p ? 0.01. This shows that there is a correlation between emotional intelligence and academic achievement of Form 4 students throughout Johor. In addition, it also shows that there is a significant relationship between emotional intelligence and student academic achievement. However, the findings of this study were also supported by the study conducted by Azizi and others (2005) which found that there was no significant correlation between the levels of extrinsic motivation of the students with the level of academic achievement of the students. The results of one-way ANOVA analysis show significant differences in overall mean of logical thinking according to academic achievement at secondary level (F (2.496) = 64.614, p <0.0005.). This finding succeeded in rejecting the second zero hypothesis stating that there was no significant difference in the mean of logical thinking ability according to the academic achievement of students at the secondary level. The findings of this study are also supported by a study conducted by Corpus (2005) which shows the correlation between extrinsic motivation and negative relationship with student academic achievement. The information obtained from this study can be used by the Ministry of Education, school administrators, Guidance Teachers and Counselling and parents in realizing the desire to produce quality human capital among teenagers in Malaysia. This information can also help researchers study their emotional intelligence, motivation and logical thinking.